Atom probe tomography of nanoporous gold formed by dealloying lean noble alloys. (December 2020) - Ebrahimy, Amir F.; Langelier, Brian; Newman, Roger C.
Abstract: Nanoporous gold (NPG) has numerous applications in (electro)catalysis, (bio)sensing, actuation, and photonics. The economic viability, however, remains a barrier to its widespread applicability. In this study, lean noble alloys (5 at. % Au) were designed and fabricated while aiming for the minimum gold content to ensure a fully Au covered surface after electrochemical dealloying. Moreover, the morphological effects of alloying with Pt were elucidated via electrochemical, microscopical, and tomographical characterization. The true surface area after dealloying was found to increase by a factor of 240 and 900 in the case of the binary (Ag95 Au5 ) and the ternary (Ag94 Au5 Pt1 ) systems, respectively. To enable atom probe tomography (APT) on such highly porous samples, the nanoporous structures were filled by Cu electrochemical depositon. APT data analysis provided various composition profiles according to which Au enrichment on ligament edges, which was more pronounced in the case of the binary samples, was detected. Future experiments on monolayer Au covered model samples are planned to obtain conclusive atomic-scale insight into the near surface composition of lean nanoporous gold structures.